Pericardial Mesothelioma in a 35-Year-Old Male With Ulcerative Colitis. (January 2019) - Iliff, James; Bart, Nicole K.; Ghaly, Simon; Granger, Emily; Holloway, Cameron J.
Abstract : Supplemental Digital Content is available in the text.